Examen especial a cuentas por cobrar y su incidencia en el flujo financiero de la empresa “oriental industria alimenticia oia Cia Ltda”; cantón Quevedo, año 2013 - Palacios Vera, Gema Sofía (2015)
In today's economy, trade is growing and essential for economic growth time, inevitably resulting in the lending process, which manages to be the base peak in trade negotiations. Most organizations perform credit sales to their customers, which represents a risk at a particular time, not to recover the capital at a precise time or maintain the execution and registration of the continuity of business operations, which could bring results in the short term capitalization. In this regard the company Oriental Food Industry OIA CIA LTDA, which is located in the Cdla. San Jose between Sixteenth and boardwalk Quevedo Canton, does not escape this reality, making most of its operations in this way, hence the interest in the analysis of receivables, in order to determine the effectiveness of the collection policies adopted and thus maintain a high level of recovery of receivables own during 2013. In terms of research methodology, methods such as inductive, deductive, analytical, synthetic and historical and logical were used since it considered that are most appropriate when you run an audit it is. As for the techniques, it became necessary to resort to observation and interview, as it is the most direct method to obtain information from the caller. The results of the analysis allowed to know that the Oriental Food Industry Company has an Internal Regulation in which policies, procedures, obligations and prohibitions of its administrative staff is detailed. Similarly it was found that not frequently evaluates the Internal Control of granted credits, according to the results of this component a confidence level of 80% (High) and a risk level of 20% (Low) was obtained, leading to be less efficient and timely so that when realize drawbacks exist that may affect Company. The lack of training of staff by Risk confidence level of 80% (High) and a risk level of 20% (Low), which does not allow effective and meet the goals set at the time of performing the work was obtained entrusted. It was also concluded by the internal control questionnaire, a confidence level of 75% (Moderate High) and a risk level of 25% (Low) was obtained, this is because in the department of Credit and Collections No continuous monitoring of customer upgrades to ensure the effectiveness of the internal control system. There are no failures at the system level but lack of monitoring and implementation of policies consistent not delay the collection activity because it does not yield reliable data, nor promote the efficiency of operations. Therefore it was recommended that the administrative management of the organization, considering the seriousness of the matter in order to apply the necessary corrections that allow the company to acquire the resources to function normally, streamlining procedures to implement them in a more efficient way and effective in order to stay in the market as national leader.